2020
DOI: 10.7124/bc.000a21
|View full text |Cite
|
Sign up to set email alerts
|

2-(Dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines: synthesis and anticancer activity

Abstract: Synthesis of a series of 2-(dichloromethyl)pyrazolo [1,5-a][1,3,5]triazines and evaluation in vitro of their anticancer activity against a panel of 60 cell lines derived from nine cancer types, namely leukemia, non-small cell lung cancer, colon cancer, CNS cancer, melanoma, ovarian cancer, renal cancer, prostate cancer, breast cancer. Methods. Organic synthesis; biological tests; spectral methods; statistical methods. Results. In vitro screening of the anticancer activity showed that 5 of 26 tested compounds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Moreover MCF-7 cells were significantly arrested in the G2/M stage. An in vivo studies of 34 in zebrafish presented non-toxic properties [36].…”
Section: Primary Anticancer Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover MCF-7 cells were significantly arrested in the G2/M stage. An in vivo studies of 34 in zebrafish presented non-toxic properties [36].…”
Section: Primary Anticancer Studiesmentioning
confidence: 99%
“…Screening studies of 2-(dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines 62-66 (Figure 13) showed potential anticancer properties against non-small cell lung cancers, colon cancers, renal cancer, etc. [36]. Screening studies of 2-(dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines 62-66 (Figure 13) showed potential anticancer properties against non-small cell lung cancers, colon cancers, renal cancer, etc.…”
Section: Primary Anticancer Studiesmentioning
confidence: 99%
“…This reagent was introduced into the chemistry of heterocyclic compounds in 1970s. [28,29] Recent publications report the use of 5 for the preparation of imidazol-2-ones, [30] pyrazolo- [1,5-a] pyrimidines, [31] pyrazolo [1,5-a] [1,3,5]triazines, [32] as well as a number of trisubstituted oxazoles. [33][34][35] The latter approach includes acylation of 5 at the amino group with acyl halides or anhydrides, followed by reaction with a primary or secondary aliphatic, or primary aromatic amine, resulting in the formation of the oxazole ring (Scheme 1E).…”
Section: Introductionmentioning
confidence: 99%
“…This challenge paved the way toward the search for new promising lung cancer therapeutic agents. It has been identified that the derivatives of sulfonamide (electronegative group), benzothiadiazine (fused ring), and dichloromethyl (electronegative group) have multifarious pharmacological activities and have potential applications in the field of medicine 4–8 . In addition, sulfonamides are identified as the first major drug to be used, and they form an integral component of more than 30 drugs used in the clinical field; 9–23 Dichloromethyl groups have been reported to show significant antiviral activity 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified that the derivatives of sulfonamide (electronegative group), benzothiadiazine (fused ring), and dichloromethyl (electronegative group) have multifarious pharmacological activities and have potential applications in the field of medicine 4–8 . In addition, sulfonamides are identified as the first major drug to be used, and they form an integral component of more than 30 drugs used in the clinical field; 9–23 Dichloromethyl groups have been reported to show significant antiviral activity 7,8 . The efficacies of benzothiadiazines in clinical applications such as schizophrenia, depression, Alzheimer's disease, Parkinson's disease, ADHD, and respiratory depression have also been recognized 24–33 …”
Section: Introductionmentioning
confidence: 99%